Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Kepuasan Kerja Pegawai P3DW Karawang - Vevi Gusniar; Sungkono (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study examines the influence of leadership and organizational culture on employee job satisfaction at P3DW Karawang. Key issues addressed include the effectiveness of leadership styles and the impact of organizational culture on job satisfaction levels. The primary objective of this research is to determine the significance of leadership and organizational culture in enhancing employee satisfaction. A quantitative approach was utilized, employing multiple linear regression analysis to assess the relationships among variables. Data were collected through structured questionnaires distributed to employees of P3DW Karawang. The results indicate that leadership and organizational culture both have a positive and significant impact on job satisfaction. Organizational culture was found to have a more dominant influence compared to leadership. These findings suggest that improving leadership practices and fostering a positive organizational culture can substantially enhance employee job satisfaction at P3DW Karawang.